Effect of different extraction solvents on the yield and enzyme inhibition (a-amylase, a-glucosidase, and lipase) activity of some vegetables - Wahyu Haryati Maser; Nur Maiyah; Muralidharan Nagarajan; Passakorn Kingwascharapong; Theeraphol Senphan; Ali Muhammed Moula Ali; Sri Charan Bindu Bavisetty (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Maser WH, Maiyah N, Nagarajan M, Kingwascharapong P, Senphan T, Ali AMM, Bavisetty SCB. 2023. Effect of different extraction solvents on the yield and enzyme inhibition (a-amylase, a-glucosidase, and lipase) activity of some vegetables. Biodiversitas 24: 3320-3331. The present study investigated the in vitro inhibition of a-amylase, a-glucosidase, and lipase, and antioxidant activities (DPPH, metal chelating, and FRAP) of Allium cepa L., Apium graveolens L., Coriandrum sativum L., and Petroselinum crispum (Mill.) Fuss using solvent 80% ethanol, absolute ethanol, acetone, methanol, n-hexane, chloroform, and hot water. The total phenolic content (TPC) and the FTIR and GC-MS characterization spectra were compared with the activities. The TPC of 80% ethanol extract in A. graveolens L. was the highest among the extracts, with 23.78 mg GAE/g extract. The 80% ethanol extract exhibited the most potent antioxidant activity on DPPH radical scavenging (A. graveolens, 125.57 mg AEAC/g extract), metal chelating (C. sativum, 92.85 mg EECC/g extract), and FRAP activities (C. sativum, 46.98 mg AEAC/g extract). The 80% ethanol extract showed the highest anti-a-amylase (P. crispum, 30.61 mmol ACE/g extract) and anti-a-glucosidase (A. cepa, 595.28 mmol ACE/g extract) activities. In comparison, the absolute ethanol extract of C. sativum showed the highest anti-lipase activity (42.10% inhibition). According to the FTIR spectra, the 80% ethanol extract of the four green leafy vegetables is predicted to have several active compounds. GC-MS identified the compounds responsible for the activity. Studies on the recovery potential of active compounds as oral agents to treat diabetes mellitus with certain solvents are very useful in producing oral agents and functional foods to prevent diabetes mellitus.